2017
DOI: 10.1128/aac.02070-16
|View full text |Cite
|
Sign up to set email alerts
|

attI1 -Located Small Open Reading Frames ORF-17 and ORF-11 in a Class 1 Integron Affect Expression of a Gene Cassette Possessing a Canonical Shine-Dalgarno Sequence

Abstract: By searching the Integrall integron and GenBank databases, a novel open reading frame (ORF) of 51 nucleotides (nts) (ORF-17) overlapping the previously described ORF-11 was identified within the attI1 site in virtually all class 1 integrons. Using a set of isogenic plasmid constructs carrying a single gene cassette (bla GES-1 ) and possessing a canonical translation initiation region, we found that ORF-17 contributes to GES-1 expression.KEYWORDS class 1 integrons, attI1 sequence, gene cassettes, expression (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…This means that cassettes can be carried at less cost at the "back" of an array but still have the potential to be shuffled to the "front" of the array. Some cassette genes lack a ribosome binding site (RBS), and ORF-11 (118) and the recently identified ORF-17 (119) in attI1 may contribute to expression if the cassette is the first in the array.…”
Section: Cassette Integration and Expressionmentioning
confidence: 99%
“…This means that cassettes can be carried at less cost at the "back" of an array but still have the potential to be shuffled to the "front" of the array. Some cassette genes lack a ribosome binding site (RBS), and ORF-11 (118) and the recently identified ORF-17 (119) in attI1 may contribute to expression if the cassette is the first in the array.…”
Section: Cassette Integration and Expressionmentioning
confidence: 99%
“…Instead of a sharp drop, we observed a steady decrease depending on the cassette position ( Figure 1—figure supplement 1a ). Previous work has shown that two short open-reading frames contained within the attI site can substantially enhance the translation of a cassette lacking a Shine–Dalgarno (SD) sequence when the cassette is located in first position ( Hanau-Berçot et al, 2002 ; Papagiannitsis et al, 2017 ), showing that cassette position can also modulate translation levels ( Hanau-Berçot et al, 2002 ; Jacquier et al, 2009 ). Interestingly, the aadB cassette contains a reduced SD box ( Figure 1—figure supplement 1b ), suggesting that the steep gradient in gentamicin resistance between first and second positions was mostly due to decreased translation.…”
Section: Resultsmentioning
confidence: 99%
“…( B ) Representation of the genomic environment of the aadB cassette when aadB is in last (WTA3) or first position (WTA5) in our arrays. The two ORFs overlapping the attI , which have been shown to improve cassette translation ( Hanau-Berçot et al, 2002 ; Papagiannitsis et al, 2017 ), are represented in color. …”
Section: Introductionmentioning
confidence: 99%
“…Instead of a sharp drop, we observed a steady decrease depending on the cassette position ( Figure S1a). Previous work has shown that two short open reading frames contained within the attI site can substantially enhance the translation of a cassette lacking a Shine-Dalgarno (SD) sequence when the cassette is located in first position (Hanau-Berçot et al, 2002;Papagiannitsis et al, 2017), showing that cassette position can also modulate translation levels (Hanau-Berçot et al, 2002;Jacquier et al, 2009). Interestingly, the aadB cassette contains a reduced SD box ( Figure S1b), suggesting that the steep gradient in gentamicin resistance between first and second position was mostly due to decreased translation.…”
Section: A Combinatorial Three-cassette Integron System To Investigamentioning
confidence: 90%
“…Representation of the genomic environment of the aadB cassette when aadB is in last (WTA3) or first position (WTA5) in our arrays. The two ORFs overlapping the attI which have been shown to improve cassette translation (Hanau-Berçot et al, 2002;Papagiannitsis et al, 2017) are represented in colour.…”
Section: Experimental Evolution With Pambl1mentioning
confidence: 99%